Listaamattomien osakeyhtiöiden verotud, voitonjako ja investoinnit; Taxation, Profit Distribution and Investment of Non-listed Companies in Finland - Niku Määttänen; Olli Ropponen (The Research Institute of the Finnish Economy (ETLA), 2014)
– This paper studies the taxation of non-listed companies and their owners in Finland. We first describe the main features of the Finnish tax system regarding the taxation of dividends from non-listed companies. We use firm-level data to illustrate how the tax incentives are reflected in firms' profit distribution policies. We then build a dynamic investment model that features the main characteristics of the Finnish dividend taxation. In the model, entrepreneurs face a borrowing constraint and have a consumption smoothing motive. We use the model to investigate how the current dividend taxation affects the investment incentives. The results illustrate how the current dividend taxation in certain cases distorts firms' investment decisions.
Keywords: D92; G35; H24; 330; Dividend taxation; Non-listed companies; Firm investment; Kapitalertragsteuer; Dividende; Investitionsentscheidung; Finnland